Complex Meniscus Tears Treated with Collagen Matrix Wrapping and Bone Marrow Blood Injection: A 2-Year Clinical Follow-Up. (April 2016) - Piontek, Tomasz; Ciemniewska-Gorzela, Kinga; Naczk, Jakub; Jakob, Roland; Szulc, Andrzej; Grygorowicz, Monika; Slomczykowski, Michal
Objective: To collect and analyze the 2-year follow-up clinical and MRI results of patients treated with an arthroscopic technique of collagen membrane-based meniscus repair. Design: 53 consecutive patients with combined (horizontal and radial or longitudinal component) and complex meniscal tears (tear extended through avascular zones or/and composed with two or more morphological tear pattern) were treated with an "all-inside" arthroscopic suture of meniscus and wrapping with a collagen membrane (Chondro-Gide) technique with bone marrow blood injection. The IKDC 2000 subjective score, IKDC 2000 clinical evaluation score, Lysholm score and Barret clinical criteria of meniscal healing were recorded. All patients were examinated by MRI 2 years postoperatively, using modified WORMS criteria for meniscal integrity. Results: The 2 year follow-up was achieved in 50 cases. Of these, 2 patients were excluded from the evaluation due to incomplete data and 2 patients underwent partial meniscectomy and were classified as failures. In 46 patients (86.8% of the intended to treat cases), a statistically significant improvement in IKDC 2000 subjective, Lysholm scores and IKDC 2000 clinical assessment between preoperative and the 2-year follow-up time points were obsereved. Barret criteria demonstrated an improved clinical outcome between pre- and post-operative values. MRI revealed a non-homogeneous signal without meniscal tear (WORMS grade 1) in 76% of the operated menisci (13% WORMS grade 2). Conclusions: The 2-year follow-up data demonstrate that this technique is safe and can offer an additional tool to save the meniscus in the patients otherwise scheduled for meniscal removal. Level of evidence IV